Supporting the regional development in the knowledge economy: the adoption of a system dynamic approach in Ghana. (6th March 2019) - Vecchio, Pasquale Del; Oppong, Nana Boakye
The adoption of a systemic and dynamic approach to innovation is a significant feature in the debate on regional development in the knowledge economy. The innovation ecosystems arise as suitable environment to address the challenges for the competitiveness of national systems as well as their successful positioning in the geography of innovation. This highlights the need of pragmatic policies and effective collaborations of government-university-industry as stipulated by the triple helix. However, the dynamic comprehension and foresight of alternative evolutionary paths available are a further challenge for scientists and decision makers, called to afford the complexity and turbulence of a socio-economic context in continuous change. Aimed at contributing to the discussion on the knowledge-based development of countries, the paper focuses on Ghana by adopting a system dynamic approach for exploring the nature and impacts of the interactions between academia (university) and industry (market), by highlighting areas of causality, relationship and addictions.